SPK Bantuan BANSOS PBI JK Menggunakan Metode PSI - Sa'idah, Fatiyah (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
The abbreviation for PBI JK is Recipients of Health Insurance Contribution Assistance, where PBI JK Social Assistance is a monthly contribution. This assistance is paid by the central government to certain communities in the health sector through BPJS Health for free without paying contributions. PBI JK which addresses the needy, the poor, the lower middle class, those who do not have a steady income, inadequate housing or those who do not have a home and many other provisions as members of the PBI JK. Problems that often occur when selecting aid recipients PBI JK social assistance at the Medan Senembah village office is manual field information collection carried out by the Medan Senembah village implementation team, resulting in a long work process. In this case, a decision support system requires a decision support system using the PSI method because this method does not need to determine the relative importance between attributes. The use of the PSI method is useful when there is a conflict in determining the relative importance between attributes. The criteria weighting assessment stages are selected based on the data in the decision matrix according to predetermined standards and the criteria weightings have been identified objectively using PSI.